2020
DOI: 10.1007/s11869-020-00916-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on variation of atmospheric pollutants over Bhubaneswar during imposition of nationwide lockdown in India for the COVID-19 pandemic

Abstract: The nationwide lockdown in India to flatten the pandemic COVID-19 curve has resulted in the reduction of anthropogenic emission sources to a great extent. This study reports change in air quality and its impact on the environment during the unique lockdown scenario at Bhubaneswar, a coastal smart city in east India. The urban air shows a remarkable reduction in the mean pollutant levels influenced by traffic emission viz. NO x (~67 %) and BC (~47 %) during lockdown over the pre-lockdown. Comparatively, a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 64 publications
1
32
1
1
Order By: Relevance
“…China: (Agarwal et al, 2020;Chauhan and Singh, 2020;Chen et al, 2020a;Chen et al, 2020c;Chen et al, 2020d;Fan et al, 2020;G Huang and Sun, 2020;Lian et al, 2020;Liu et al, 2020c;Miyazaki et al, 2020;Nichol et al, 2020;Pei et al, 2020;Shakoor et al, 2020;Shi and Brasseur, 2020;Silver et al, 2020;Wan et al, 2020;Wang et al, 2020a;Wang et al, 2020b;Wang et al, 2020f;Xu et al, 2020c;Zhang et al, 2020a;Yuan et al, 2021) Other: (Ghahremanloo et al, 2020;Han et al, 2020;Ju et al, 2020;Ma and Kang, 2020;Zhang et al, 2020b) South Asia India: (Bedi et al, 2020;Beig et al, 2020;Biswal et al, 2020;Chatterjee et al, 2020;Gautam et al, 2020;Harshita and Vivek, 2020;Jain and Sharma, 2020;Kant et al, 2020;Kumari and Toshniwal, 2020;Panda et al, 2020;Ranjan et al, 2020;Selvam et al, 2020;Sharma et al, 2020a;Siddiqui et al, 2020;Singh and Chauhan, 2020;…”
Section: East Asiaunclassified
See 1 more Smart Citation
“…China: (Agarwal et al, 2020;Chauhan and Singh, 2020;Chen et al, 2020a;Chen et al, 2020c;Chen et al, 2020d;Fan et al, 2020;G Huang and Sun, 2020;Lian et al, 2020;Liu et al, 2020c;Miyazaki et al, 2020;Nichol et al, 2020;Pei et al, 2020;Shakoor et al, 2020;Shi and Brasseur, 2020;Silver et al, 2020;Wan et al, 2020;Wang et al, 2020a;Wang et al, 2020b;Wang et al, 2020f;Xu et al, 2020c;Zhang et al, 2020a;Yuan et al, 2021) Other: (Ghahremanloo et al, 2020;Han et al, 2020;Ju et al, 2020;Ma and Kang, 2020;Zhang et al, 2020b) South Asia India: (Bedi et al, 2020;Beig et al, 2020;Biswal et al, 2020;Chatterjee et al, 2020;Gautam et al, 2020;Harshita and Vivek, 2020;Jain and Sharma, 2020;Kant et al, 2020;Kumari and Toshniwal, 2020;Panda et al, 2020;Ranjan et al, 2020;Selvam et al, 2020;Sharma et al, 2020a;Siddiqui et al, 2020;Singh and Chauhan, 2020;…”
Section: East Asiaunclassified
“…, 2020),(Zhang et al, 2020d), United Kingdom:(Higham et al, 2020),(Fu et al, 2020;Zhang et al, 2020d), Russia:(Fu et al, 2020), Italy:(Fu et al, 2020), France:(Fu et al, 2020),(Zhang et al, 2020d), Spain:(Fu et al, 2020),(Martorell-Marugán et al, 2021),(Zhang et al, 2020d), and Germany:(Zhang et alet al, 2020a;Chen et al, 2020d;Jia et al, 2020b;Liu et al, 2020c;Qiu et al, 2020;Yuan et al, 2021), India:(Chatterjee et al, 2020;Panda et al, 2020), Italy:(Collivignarelli et al, 2020), United Kingdom: (Ropkins and Tate, 2020), Canada: (Adams, 2020), United States:(Xiang et al, 2020), and Brazil:(Nakada and Urban, 2020;Siciliano et al, 2020b) AOD India:(Gautam, 2020b;Ranjan et al, 2020;Zhang et al, 2020d), China(Diamond and Wood, 2020;Ghahremanloo et al, 2020;Zhang et al, 2020d;Shen et al, 2021), South Korea, and Japan(Ghahremanloo et al, 2020), North America, and Europe(Zhang et al, 2020d) NMVOCs China:(Ghahremanloo et al, 2020;Jia et al, 2020b;Qiu et al, 2020), South Korea:(Ghahremanloo et al, 2020), Japan:(Ghahremanloo et al, 2020;Zhang et al, 2020b), India:(Beig et al, 20...…”
mentioning
confidence: 99%
“…As the lockdown situation is being implemented nation-wide, the transported anthropogenic component could be less than that of the pre-lockdown period. A similar study over Bhubaneswar (a city along the east coast of India) reported a 47% reduction in BC during the lockdown period when compared to the pre-lockdown level ( Panda et al, 2020 ). Moreover, the generally present prominent bimodal peaks in the diurnal variation of BC were not observed during the lockdown period.…”
Section: Discussionmentioning
confidence: 94%
“…A few studies have been conducted to reveal the impacts of COVID-19 lockdown measures on ambient BC concentrations. Reported studies from the USA [66], Italy [67], China [68,69], and India [70] revealed that BC concentrations reduced within the range between 22% and 71% in response to lockdown measures to combat the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%